ENVOLVER+: a tool for the promotion of positive nursing practice environments - Ribeiro, Olga Maria Pimenta Lopes; Schacht, Ligia; Gonçalves, Mariana Filipa Mendes; Faria, Ana da Conceição Alves; Ribeiro, Marlene Patrícia; Ventura-Silva, João Miguel Almeida (Frontiers in Public Health, 2025)
IntroductionPatients, nurses, and the organization itself can benefit from a good work environment. One of the weaknesses most often cited by nurses was the lack of involvement and participation in setting workplace policies. Using games is a promising strategy for promoting positive caregiving environments. The purpose of this study is to describe the process by which the ‘ENVOLVER+’ board game has been developed and validated.MethodsWe carried out a methodological study from September 2023 to May 2024 in three phases: (1) modified e-Delphi to validate the content to be included in the game; (2) development of the prototype board game; (3) application of the game in four practice contexts.ResultsThe four sessions of the ‘ENVOLVER+’ game lasted an average of 80 min. Each session had twelve participants in four groups. At the end of the sessions, we asked the participants to comment on the advantages and disadvantages of the game.DiscussionThe ‘ENVOLVER+’ game can be a valuable tool in promoting a positive nursing practice environment by providing an innovative and interactive approach to ensuring nurse involvement and participation.